Potency of tubers and rhizomes of Java local foods as prebiotics and their effects toward bacterial diversity in mice cecum - YUDHA WASKITA; ARTINI PANGASTUTI; SHANTI LISTYAWATI; SITI LUSI ARUM SARI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Waskita Y, Pangastuti A, Listyawati S, Sari SLA. 2024. Potency of tubers and rhizomes of java local foods as prebiotics and their effects toward bacterial diversity in mice cecum. Biodiversitas 25: 1544-1553. Tubers and rhizomes (TR) as Java local foods were less attention by people. Local foods contain IP (indigestible polysaccharides) content as prebiotic. The study aimed to analysis the prebiotic potency of TR extracts based on IP content and their effects toward increasing probiotic bacterial number, the TR extracts toward short-chain fatty acid (SCFA) profiles in probiotic media, and the TR extracts toward SCFA profiles and bacterial diversity in mice cecum. Tubers used were purple yam (Dioscorea alata var. purpurea), air potato (D. bulbifera), porang (Amorphophallus muelleri), Asiatic yam (D. esculenta), Asiatic bitter yam (D. hispida), white spot giant arum (A. paeoniifolius), yam bean (Pachyrizus erosus), and Hausa potato (Coleus rotundifolius). Rhizomes used were taro (Colocasia esculenta), arrowroot (Maranta arundinacea), and canna lilly (Canna indica). Work steps were extraction of TR, DNS assay, total sugar assay after acidic and enzymatic digestion, stimulation on increasing probiotic bacterial number (Lactobacillus plantarum and Bifidobacterium bifidum), SCFA production of probiotics, mice treatment, SCFA extraction in cecum, and determination of cecum bacterial communities. The highest IP contents were arrowroot, purple yam, air potato, porang, Asiatic yam, and taro extracts. These extracts except taro have higher IP content than inulin. The highest increasing probiotic bacterial number and SCFA production were shown by arrowroot extract rather than purple yam, air potato, and inulin. Bacteria communities had a high diversity value that showed micro-ecosystem balance in the cecum. Arrowroot was the same with inulin in increasing probiotics SCFA producers (Lachnospiraceae NK4A136, [Ruminococcus], Lactobacillus, Bacteroides, and Bifidobacterium) and decreasing pathogenic bacteria (Lachnoclostridium, Helicobacter, and Lawsonia) in mice cecum compared with control feed. Mucispirillum as a pathobiont-commensal had the same abundance in three feed treatments. Bacteria fermentation in the cecum produced the highest SCFA concentration in the 5% arrowroot feed treatment. Arrowroot had better prebiotic potency for the future.